Land Use and Stream Nitrogen Concentrations in Agricultural Watersheds Along the Central Coast of California. (2001) - Los Huertos, Marc; Gentry, Lowell E.; Shennan, Carol
Abstract : In coastal California nitrogen (N) in runoff from urban and agricultural land is suspected to impair surface water quality of creeks and rivers that discharge into the Monterey Bay Sanctuary. However, quantitative data on the impacts of land use activities on water quality are largely limited to unpublished reports and do not estimate N loading. We report on spatial and temporal patterns of N concentrations for several coastal creeks and rivers in central California. During the 2001 water year, we estimated that the Pajaro River at Chittenden exported 302.4 Mg of total N. Nitrate-N concentrations were typically <1 mg N l–1 in grazing lands, oak woodlands, and forests, but increased to a range of 1 to 20 mg N l–1 as surface waters passed through agricultural lands. Very high concentrations of nitrate (in excess of 80 mg N l–1 ) were found in selected agricultural ditches that received drainage from tiles (buried perforated pipes). Nitrate concentrations in these ditches remained high throughout the winter and spring, indicating nitrate was not being flushed out of the soil profile. We believe unused N fertilizer has accumulated in the shallow groundwater through many cropping cycles. Results are being used to organize landowners, resource managers, and growers to develop voluntary monitoring and water quality protection plans.